The Short Version of the Metacognitive Anger Processing Scale (MAP-SV) – initial psychometric testing. Issue 1 (3rd January 2022) - Moeller, Stine Bjerrum; Juul, Sophie; Arendt, Ida-Marie T. P.
Abstract: Background: The 26-item version of the Metacognitive Anger Processing Scale (MAP) has shown good psychometric properties in previous studies. However, there is a need for a shorter version of the scale. Aims: The aim of the present study is to psychometrically evaluate the 9-item Metacognitive Anger Processing Scale – Short Version (MAP-SV) in comparison with the original, 26-item version. Method: The 26-item MAP includes three subscales: rumination, positive beliefs and negative beliefs. Three items from each subscale were selected based on clinical validity to constitute the 9-item MAP-SV. A previous sample used for validation of the 26-item MAP was used for clinimetric testing. The sample included psychiatric patients ( n = 88) and male forensic inpatients ( n = 54). The MAP-SV was assessed according to scalability, convergent validity with general metacognition, and concurrent validity with anger measures. Results: The scalability of the 9-item MAP-SV was comparable to that of the original 26-item MAP in most psychometric tests. The Loevinger's coefficient of homogeneity for the total score of the MAP-SV items was 0.29 for the combined sample compared with 0.36 in the original MAP, indicating close to acceptable scalability. The alpha coefficient for the MAP-SV total score was 0.79. For the combined sample, Pearson inter-correlations between the subscales of the MAP-SV were highly correlated with the MAP-SV total score (ranging from .66 to .84). Conclusions: The 9-item MAP-SV showed good psychometric properties and can be used as a reliable tool for assessing self-reported metacognitive anger processing.